Meningoradiculitis and Immune Mediated Myositis in a Patient with Lyme disease: A Case Report of a Probably Underestimated Association - Ezaru, Andra; Grecu, Nicolae; Villa, Luisa; Durant, Jacques; Cavalli, Michele; Sacconi, Sabrina; Puma, Angela (Archives of Clinical and Biomedical Research, 2021)
We describe the association of cervical meningoradiculitis and focal immune mediated myositis secondary to Borrelia infection in a 62 year old immune competent patient. Diagnosis was made by lumbar puncture, nerve conduction studies and muscle magnetic resonance imaging (MRI). Cerebrospinal fluid (CSF) analysis found evidence of an inflammatory process with elevated production of Borrelia IgG antibodies. Deltoid muscle biopsy detected the presence of spirochetal DNA with immunohistochemical changes corresponding to dermatomyositis. The clinical – pathological associations made in this case can help clarify the intricate processes that take place on a cellular level in patients with Lyme disease.